Pembuatan Batik Dengan Teknik Pewarnaan Colet Sebagai Upaya Pelestarian Budaya dan Pemberdayaan Masyarakat - Alvin Yuda Sadewa; Alan Surya Wijaya; Viki Nurlatifah; Hilma Amalia; Sri Lestari; Raihan Muhammad Iqbal; Zakiyatul Badriyah; Fatih Akbar Rafsanjani; Irfan Fadhilah; Khikmah Fatma Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Batik comes from the root word 'tik' which means dot. Basically, batik means dotted, while batik means to make dots. In Javanese, dots are called cecek, which is an important part of batik. Batik is an intangible cultural heritage that has been designated by UNESCO since 2009. Therefore, efforts are needed to develop batik in people's lives. One effort that can be made to preserve culture is to modify and maintain the existence of that culture. The aim of this batik training is to improve the economy of the Dukuh Simo community because in the batik training the training participants directly practice how to make batik using the dabbing technique. This training directly involved the Dukuh Simo community, consisting of PKK women. In this research the author used a qualitative descriptive approach. Data collection techniques used are observation, interviews, and documentation. It is hoped that the results of this research will increase the knowledge and economy of residents and ensure that batik remains a culture that has been preserved for generations.